CHEMICAL COMPOSITION OF ESSENTIAL OILS OF ROOTS AND LEAVES OF FERULA TADSHIKORUM PIMENOV - Dilovar Tolibdjonovna Khamraeva; Dinara Navruzovna Tukhtaeva; Olim Kaxxarovich Khojimatov; Rainer Willi Bussmann; Sodikzhon Kholiknazarovich Abdinazarov (Химия растительного сырья, 2025)
This study describes the results of a comparative analysis of the chemical composition of essential oils of roots and leaves of 3 samples of virginile plants Ferula tadshikorum of various years of life from natural places (12–14 and 24–27-year-old individuals, Babatag ridge of the Surkhandarya region) of growth and in culture (4 years of life, Tashkent Botanical Garden).The chemical composition of essential oils obtained by hydrodistillation was relatively investigated by means of GC-MSD analysis.The results obtained showed that the isolated chemicals differ and are related to the age of plants. For example, introduced plants had an almost similar qualitative composition of essential oils of leaves and roots, and in natural individuals, the leaves, irrespective of the age of the plant, contained the same main components, while the roots had a different compound composition. The main component of the essential oils of the introducents were myristicin and methanethioamide, N,N-dimethyl, and in individuals of natural habitats the sulfur-containing components were thiopropionamide; disulfide, methyl 1-(methylthio) propyl and 1-(1-Propen-1-yl)-2-(2-thiopent-3-yl) disulfide, and also Germacyclobutane, 1,1-dimethyl-.According to the available literature, they have anti-cancer, antioxidant and antimicrobial activity, and in the future research should be aimed at studying their therapeutic abilities.